Thyme oil inclusion levels in a rabbit ration: Evaluation of productive performance, carcass criteria and meat quality under hot environmental conditions - Abdel-Wareth, Ahmed A.A. (Anim Nutr, 2018)
The aim of this study was to determine the impact of thyme essential oil supplementation in rabbit rations on performance, carcass criteria, and meat quality under hot environmental conditions. A total of 75, 4-week-old Californian male rabbits were assigned to 5 dietary treatments until 12 weeks of age. The rabbits were reared in an open house system (38 °C average ambient temperature and 26% to 35% relative humidity). Treatments were as follows: unsupplemented standard ration, negative control (CON); standard ration supplemented with 1.50 g/kg olive oil as carrier, positive control (POS); POS + 50 mg/kg thyme oil (TO1); POS + 100 mg/kg thyme oil (TO2); and POS + 150 mg/kg thyme oil (TO3). Dietary thyme oil up to 150 mg/kg improved (P < 0.001) feed intake and growth performance in comparison to CON. The highest average daily gain and most efficient feed conversion ratio (linear, P < 0.001 and quadratic, P < 0.001) were found for TO1 followed by TO2, TO3 and POS, respectively. The incorporation of thyme oil improved (P < 0.001) carcass criteria and decreased (P < 0.001) perirenal and scapular fat without any side effects on internal organs. Notably, the water holding capacity of rabbit meat was greater (P < 0.001), and the lipid oxidation was lower (P < 0.01) in rabbits fed treated rations compared with CON. Differences were also recorded in oxymyoglobin and metmyoglobin contents in rabbit meat among treatments. In conclusion, thyme oil of a specified composition and to be added to a rabbit ration up to 100 mg/kg using 1.50 g/kg olive oil as a carrier can be used as an efficient feed additive for improving productive performance of rabbits under hot environmental conditions.